2010
DOI: 10.1007/s00586-010-1377-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Internet use amongst an elective spinal surgery outpatient population

Abstract: Nationally 62% of individuals in Ireland have internet access. Previous published work has suggested that internet use is higher among those with low back pain. We aimed to determine the levels of internet access and use amongst an elective spinal outpatient population and determine what characteristics influence these. We distributed a self-designed questionnaire to patients attending elective spinal outpatient clinics. Data including demographics, history of surgery, number of visits, level of satisfaction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 8 publications
(7 reference statements)
1
34
0
Order By: Relevance
“…We first aimed to determine the level of internet use in our cohort of parents of children attending the scoliosis outpatient clinic. Confirming our hypothesis we found that the prevalence of internet use of almost 60 % was much greater than that previously encountered in an adult population with spinal complaints [2]. It was also higher than the 39 % prevalence in a general pediatric outpatient population reported in 2002 [9].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…We first aimed to determine the level of internet use in our cohort of parents of children attending the scoliosis outpatient clinic. Confirming our hypothesis we found that the prevalence of internet use of almost 60 % was much greater than that previously encountered in an adult population with spinal complaints [2]. It was also higher than the 39 % prevalence in a general pediatric outpatient population reported in 2002 [9].…”
Section: Discussionsupporting
confidence: 85%
“…A questionnaire based on a previously used model by Baker et al [2] was used to collect basic demographic information and information regarding internet use and access. The new questionnaire was initially trialed on 20 parents attending the outpatient clinic to test for readability.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 We have performed a cross-sectional descriptive study which aims to quantify internet usage by orthopaedic outpatients in both private orthopaedic clinics as well as public hospital outpatient clinics, bringing an up-to-date perspective to studies previously carried out in this area. [6][7][8][9][10][11][12] We used surveys which targeted three main domains: 1) patient demographics; 2) general internet usage; 3) internet usage directed towards the patient's current orthopaedic condition. In this last domain we surveyed patients' perceptions of the quantity and quality of information they found related to their condition, the degree to which the information they found on the internet correlated with the information provided to them by their surgeon, and to what degree internet-based resources shaped the questions they asked of their surgeon.…”
Section: Introductionmentioning
confidence: 99%